Student’s Perception of TikTok for English Languange Learning - Muhammad Rafi Zidan; Ahmad Julianto; Alvin Maulana; Abdul Syahid (Pusat Riset dan Inovasi Nasional, 2023)
There's a lot of media that can be used to learn English independently, you can either consciously seek for the material or you can unconsciously learn about it and one of the media is social media. This research aims to know and described students perception about using Tiktok for enhancing English language learning, Using quantitative research methodology, this study explores the influence of TikTok usage on English language learning perceptions among 30 ELL students in an Indonesian university. Utilizing a questionnaire, the research evaluates three aspects of social media's impact on English learning, have a significant correlation between Tiktok usefulness and it's effectiveness for English language learning, however as for the future interest of using Tiktok for English language learning the results show that it is insignificant means that Tiktok cannot be used for learning sources in the future.